Basic aspects the translation of political terms from Turkish into Russian - Шaдкaм З.; Кaсымовa М. A. (Journal of Oriental Studies, 2017)
The novelty of this study is to use the methods and techniques of translation from a foreign language, in this case with the Turkish. This article deals with the aim and object of the translation of political terms. Types of translation of words and expressions. Peculiarities of translation of political terms. The main aspects of this article is to study the etymology of some of the political terms of the Turkish language, as well as the characteristics and difficulties of translation them into Russian.